2021
DOI: 10.1007/s13311-021-01093-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of EQ-6, a Novel Analogue of Ethoxyquin to Prevent Chemotherapy-Induced Peripheral Neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and often dose-limiting side effect of many cancer drugs. Because the onset of neuronal injury is known, it is an ideal clinical target to develop neuroprotective strategies. Several years ago, we had identified ethoxyquin as a potent neuroprotective drug against CIPN through a phenotypic drug screening and demonstrated a novel mechanism of action, inhibition of chaperone domain of heat shock protein 90. To improve its drug-like properties we synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…If EQ-6 is identified to exert neuroprotective effects in animal models of CNS diseases as well, it might be worth developing and utilizing EQ-6 as a promising pharmacological approach to prevent neurodegeneration, given that EQ-6 is likely to accumulate in neural tissue and lacks significant genotoxicity and carcinogenicity. 51 Other strategies that can also reduce SF3B2 levels include anti-sense oligos, which have been shown to be effective in several neurodegenerative studies including spinal muscular atrophy and amyloid neuropathy. 53,54 A major challenge in developing therapies for CNS axonal protection is targeting the appropriate cell types while reducing complications due to off-target side effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If EQ-6 is identified to exert neuroprotective effects in animal models of CNS diseases as well, it might be worth developing and utilizing EQ-6 as a promising pharmacological approach to prevent neurodegeneration, given that EQ-6 is likely to accumulate in neural tissue and lacks significant genotoxicity and carcinogenicity. 51 Other strategies that can also reduce SF3B2 levels include anti-sense oligos, which have been shown to be effective in several neurodegenerative studies including spinal muscular atrophy and amyloid neuropathy. 53,54 A major challenge in developing therapies for CNS axonal protection is targeting the appropriate cell types while reducing complications due to off-target side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found that ethoxyquin (EQ) and its novel analog, EQ‐6 (6‐(5‐amino)‐ethoxy‐2,2,4‐trimethyl‐1,2‐dihydroquinoline hydrochloride), prevent axonal degeneration induced in rat dorsal root ganglion (DRG) neurons treated with cisplatin or paclitaxel and mouse models of chemotherapy‐induced peripheral neuropathy (CIPN) 7,51,52 . EQ is an FDA‐approved food preservative, and it is added in animal feed 51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EQ-6 (6-(5-amino)-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline hydrochloride), a novel analog of the known antioxidant ethoxyquin, prevents axonal degeneration in primary DRG neurons and epidermal nerve fiber loss in vitro and in a murine model of paclitaxel-induced CIPN, respectively. Cetinkaya-Fisgin et al demonstrated that this axonal protection is associated with preserved levels of nicotinamide adenine dinucleotide, a key metabolite in the programmed pathway of axonal degeneration [115].…”
Section: Future Preventive Approaches Numerous Literature Reports Hav...mentioning
confidence: 99%